Public perspective on renewable and other energy resources: Evidence from social media big data and sentiment analysis - Dahye Jeong; Syjung Hwang; Jisu Kim; Hyerim Yu; Eunil Park (Energy Strategy Reviews, 2023)
To address global climate change, many countries are reducing CO2 emissions and replacing conventional energy resources with alternative ones. When developing national energy plans, it is essential to investigate public perspectives on the relationship between renewable and other energy resources. This study employs sentiment and correlation analyses of social media data to assess public perspectives on the complex relationships between renewable and other energy resources. The results show that renewable energy and nuclear energy have a complementary relationship in terms of positive emotions, but a substitute relationship in terms of negative emotions. These findings can inform regional and national energy plans and policies for renewable and nuclear energy. Additionally, this study demonstrates that the proposed methodology can be used to assess public perspectives on various energy resources.